2007
DOI: 10.1177/1087054707308496
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Symptoms of ADHD Among College Students in China and the United States

Abstract: ADHD symptomatology is present among college students in China in a pattern similar to that found in American college students. The WURS and the CSS appear to be effective screening measures for the disorder in China, although further research on gender and cultural differences is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 37 publications
(44 reference statements)
4
27
3
Order By: Relevance
“…Our results provide support for the use of the CPT-II (specifically the clinical confidence index) and CAARS (specifically the Total DSM symptoms Scale and the ADHD Index) in future studies to discriminate individuals with clinical levels of ADHD symptoms, regardless of whether they have been diagnosed in the past. Contrary to previous research of self-concept in college students with ADHD (Dooling-Litfin & Rosen, 1997; Norvilitis et al, 2008) current results revealed no significant differences between college students with and without an ADHD diagnosis on measures of academic performance (GPA), total self-concept (TSC; TSCS:2), or total psychological well-being (PWB). Although a significant positive correlation was found between TSC and PWB, self-concept for the two groups was predicted by different aspects of well-being.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results provide support for the use of the CPT-II (specifically the clinical confidence index) and CAARS (specifically the Total DSM symptoms Scale and the ADHD Index) in future studies to discriminate individuals with clinical levels of ADHD symptoms, regardless of whether they have been diagnosed in the past. Contrary to previous research of self-concept in college students with ADHD (Dooling-Litfin & Rosen, 1997; Norvilitis et al, 2008) current results revealed no significant differences between college students with and without an ADHD diagnosis on measures of academic performance (GPA), total self-concept (TSC; TSCS:2), or total psychological well-being (PWB). Although a significant positive correlation was found between TSC and PWB, self-concept for the two groups was predicted by different aspects of well-being.…”
Section: Discussioncontrasting
confidence: 99%
“…Only two studies have evaluated self esteem in college students with ADHD, and both studies used the Rosenberg Self-Esteem Scale (SES; Rosenberg, 1965), a 10-item scale measuring global self-concept. Results indicated that higher ADHD symptoms in college students were associated with greater depression and lower self esteem (Norvilitis, Ingersoll, Zhang, & Jia, 2008), and that college students with a history of ADHD scored lower on ratings of self esteem relative to controls (Dooling-Litfin & Rosen, 1997). In the latter study, within group comparisons revealed that students with ADHD who reported protective factors (better social skills, possessing a special talent and prior positive mentorship experiences) also reported higher levels of self esteem.…”
mentioning
confidence: 76%
“…For example, Norvilitis et al [2008] recently examined ADHD symptoms among college students in China and the United States. Results revealed that 4.4% of American student participants and 7.8% of Chinese students reported significant ADHD symptoms in their current functioning.…”
Section: Prevalence Of Adhd and Adhd Symptoms In College Studentsmentioning
confidence: 99%
“…Follow-up studies, however, have found that the majority of individuals who are diagnosed with ADHD in childhood continue to display symptoms of the disorder into adulthood (Barkley, Fischer, Smallish, & Fletcher, 2002). Preliminary studies suggest that a significant percentage of college students report symptoms associated with ADHD and that college students with ADHD are at risk for academic difficulties, psychological adjustment difficulties, and problems with internal restlessness (Norvilitis, Ingersoll, Zhang, & Jia, 2008;Rabiner, Anastopoulos, Costello, Hoyle, & Swartzwelder, 2008;Weyandt & DuPaul, 2006;Weyandt et al, 2003).…”
mentioning
confidence: 99%